2021
DOI: 10.3389/fonc.2021.720044
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival of Patients With Unresectable or Metastatic BRAF V600-Mutant Acral/Cutaneous Melanoma Administered Dabrafenib Plus Trametinib: Long-Term Follow-Up of a Multicenter, Single-Arm Phase IIa Trial

Abstract: ObjectivesTo examine the long-term survival outcome of dabrafenib in combination with trametinib in Chinese patients with unresectable or metastatic acral/cutaneous melanoma with BRAF-V600 mutation and to explore potential predictors of effectiveness.MethodsThis was a long-term follow-up of Chinese patients with unresectable or metastatic BRAF V600-mutant acral/cutaneous melanoma administered dabrafenib (150 mg twice daily) plus trametinib (2 mg once daily) in an open-label, multicenter, single-arm, phase IIa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…With long-term follow-up of the Chinese patients identified in multicenter phase IIa trial for Dabrafenib plus Trametinib conducted in East Asia, ORR reached as 71.7% and PFS was 9.3 months, which was comparable to the data from the clinical trials with Caucasian population. 27 Our study still has several important limitations. First of all, it is a retrospective study with relatively small sample of patients in each treatment group.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…With long-term follow-up of the Chinese patients identified in multicenter phase IIa trial for Dabrafenib plus Trametinib conducted in East Asia, ORR reached as 71.7% and PFS was 9.3 months, which was comparable to the data from the clinical trials with Caucasian population. 27 Our study still has several important limitations. First of all, it is a retrospective study with relatively small sample of patients in each treatment group.…”
Section: Discussionmentioning
confidence: 90%
“…With long‐term follow‐up of the Chinese patients identified in multicenter phase IIa trial for Dabrafenib plus Trametinib conducted in East Asia, ORR reached as 71.7% and PFS was 9.3 months, which was comparable to the data from the clinical trials with Caucasian population. 27 …”
Section: Discussionmentioning
confidence: 99%
“…These results may imply that BRAF/MEK inhibitors can exert efficacy for acral melanoma (including NAM) comparable to that for cutaneous melanoma. Other case series may also support this notion [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. However, the long-term efficacy of targeted therapies remains unclear.…”
Section: Treatmentmentioning
confidence: 82%
“…A retrospective study from South Korea reported similar results (objective response rate of 78.9% in 10 acral/mucosal melanomas) [ 116 ]. Furthermore, a single-arm phase II trial in China (12 acral, 41 non-acral cutaneous, and 7 unknown primary melanomas) reported the efficacy of dabrafenib/trametinib combination therapy; the 3-year overall survival was 28.8% in the overall population and 35.7% in acral melanoma patients [ 117 ]. These results may imply that BRAF/MEK inhibitors can exert efficacy for acral melanoma (including NAM) comparable to that for cutaneous melanoma.…”
Section: Treatmentmentioning
confidence: 99%
“…[3][4][5] Immunotherapy (pembrolizumab, nivolumab, nivolumab plus ipilimumab, and nivolumab plus relatlimab) as a standard first-line therapy for advanced cutaneous melanoma 6 yields modest efficacy in advanced AM. [7][8][9][10][11] Despite the favorable efficacy of treatment with BRAF inhibitors combined with MEK inhibitors in patients with BRAF V600 -mutant advanced melanoma, 12,13 infrequent variants of BRAF (10%-22%) and NRAS (9%-28%) in AM limited the use of this combination. [3][4][5]14,15 KIT variants are primarily found in mucosal and acral melanomas, but also with a low frequency (10%-20%).…”
mentioning
confidence: 99%